Corrosion behavior of diamond-like carbon film induced by Al/Ti co-doping - Xu, Xiaowei; Zhou, Yong; Liu, Linlin; Guo, Peng; Li, Xiaowei; Lee, Kwang-Ryeol; Cui, Ping; Wang, Aiying (ELSEVIER, 2020)
Diamond-like carbon films with Al and Ti dopants (Al/Ti-DLC) were fabricated by a hybrid ion beam deposition system combined with a special design of splicing targets, in which the Al/Ti ratio was changed from 4.0 to 1.1 by tailoring the Al content. The structural evolution and corrosion behavior of Al/Ti-DLC films in 3.5 wt% NaCl solution were systematically investigated by comparing with the 316L SS and pure DLC film. Results revealed that compared with the pure DLC and 316L SS substrate, the Al/Ti-DLC film exhibited enhanced corrosion resistance by reducing the porosity and increasing the barrier for both the charge transfer and the diffusion of corrosive ions into the substrate. In particular, the anti-corrosion behavior of DLC film highly depended on the Al/Ti ratio, which decreased gradually with the Al/Ti ratio ranged from 4.0 to 1.1. Structural and EIS analysis indicated that this was ascribed to both the increased residual stress and sp(2) hybridized fraction, which induced not only the formation and propagation of cracks during the corrosion process but also the high electric conductivity and low diffusion barrier of corrosive ions, accelerating the corrosion processes at the film/substrate interface.
Keywords: DLC FILMS; TRIBOLOGICAL PROPERTIES; SURFACE CHARACTERISTICS; RESISTANCE PROPERTIES; STAINLESS-STEEL; AB-INITIO; COATINGS; PROTECTION; WEAR; TI